Ion transporter cascade, reactive astrogliosis and cerebrovascular diseases - Rahman, Md Shamim; Islam, Rabia; Bhuiyan, Mohammad Iqbal H. (Frontiers in Pharmacology, 2024)
Cerebrovascular diseases and their sequalae, such as ischemic stroke, chronic cerebral hypoperfusion, and vascular dementia are significant contributors to adult disability and cognitive impairment in the modern world. Astrocytes are an integral part of the neurovascular unit in the CNS and play a pivotal role in CNS homeostasis, including ionic and p H balance, neurotransmission, cerebral blood flow, and metabolism. Astrocytes respond to cerebral insults, inflammation, and diseases through unique molecular, morphological, and functional changes, collectively known as reactive astrogliosis. The function of reactive astrocytes has been a subject of debate. Initially, astrocytes were thought to primarily play a supportive role in maintaining the structure and function of the nervous system. However, recent studies suggest that reactive astrocytes may have both beneficial and detrimental effects. For example, in chronic cerebral hypoperfusion, reactive astrocytes can cause oligodendrocyte death and demyelination. In this review, we will summarize the (1) roles of ion transporter cascade in reactive astrogliosis, (2) role of reactive astrocytes in vascular dementia and related dementias, and (3) potential therapeutic approaches for dementing disorders targeting reactive astrocytes. Understanding the relationship between ion transporter cascade, reactive astrogliosis, and cerebrovascular diseases may reveal mechanisms and targets for the development of therapies for brain diseases associated with reactive astrogliosis.